9=3g

Simple and best practice solution for 9=3g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=3g equation:


Simplifying
9 = 3g

Solving
9 = 3g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-3g' to each side of the equation.
9 + -3g = 3g + -3g

Combine like terms: 3g + -3g = 0
9 + -3g = 0

Add '-9' to each side of the equation.
9 + -9 + -3g = 0 + -9

Combine like terms: 9 + -9 = 0
0 + -3g = 0 + -9
-3g = 0 + -9

Combine like terms: 0 + -9 = -9
-3g = -9

Divide each side by '-3'.
g = 3

Simplifying
g = 3

See similar equations:

| 180=16x-3+45 | | 5x+1-2x=27 | | 0.75y=2x-6 | | 2(y+2)-8=0 | | -4x^2+19x=-320 | | x+1-4x=13 | | 5/8q=-20 | | 8x-13y=12 | | Y-5=m(x-6)form | | -18=-x-11 | | 8y+y^2=180 | | 8y+y^2=189 | | 0.54(6)+.06x=.18(24+x) | | f(4)=9x+7 | | -8+6x+4x=-98 | | 13x+1=9x+5 | | 3(c-63)=27 | | 5x-9+3x=87 | | f(5)=3x+x^2 | | (X-2)/10=(x-7)/5 | | X+325=520 | | f(x)=3x+x^2 | | 4x+10-2x=-10 | | 3(k+9)=72 | | -t+-6=-10 | | 32(x-1)+115x+10(x+2)=1607 | | -24=8(r+63) | | 43=2x+2x+7 | | 3/7x3 | | 3h+2=-4 | | -2x-2+5x=16 | | 4(b-73)+44=60 |

Equations solver categories